Efektivitas Penggunaan Es Batu pada Pengiriman Lobster Air Tawar (Cherax Quadricarinatus) - Ikhsan Maulana Anwari; Novita MZ; Arif Supendi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The high mortality in crayfish shipping transportation activities is due to the high level of stress during transportation. The handling that needs to be considered is when harvesting and transporting the fry. Poor seed transportation can result in stress to high mortality. Transportation of live crayfish can be done in two ways, namely with a wet system using water and a dry system without using water media. Research to maintain mortality begins with packing procedures starting from placing ice cubes in plastic that has been wrapped in newspaper in each 500ml seteroafoam and then inserting 22 crayfish in each box and then allowed to stand with a predetermined deadline. The first treatment survival rate reached 97% of 66 mortalities of 2 tails, in the second treatment 94% of 66 mortalities of 4 tails, the third treatment 80%, of 66 mortalities of 9 tails. Based on the results of the study, the addition of ice cubes to the packing media for crayfish with living conditions resulted in an average survival rate of 90.3% with the shortest deadline of 30 hours and the longest of 40 hours, thus it can be said that the packing media with the addition of ice cubes has an impact on the survival rate of crayfish.